The Archaeology of Northern Slavery and Freedom - Delle, James A. (Book collections on Project MUSE., 2019)
Although African slavery in the United States is generally associated with the South, the institution also existed in northern states as late as the 1840s, especially in large urban centers, such as Philadelphia and New York. Contrariwise, freed African Americans in the region established rural communities all their own and actively resisted the institution as a whole. The newest volume proposed for inclusion in the American Experience in Archaeological Perspective series, written by one of the leading scholars in the field of African Diaspora archaeology, is a synthetic analysis of recently published work on the subject (although no monograph exists on northern slavery). This volume provides a new perspective on the intricate connection between slavery and freedom in the United States. As Delle argues, scholars cannot understand slavery "in the absence of freedom."